2019
DOI: 10.1002/humu.23757
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic mutation in MYH7 and MYBPC3 leads to severe cardiomyopathy with left ventricular noncompaction phenotype

Abstract: Dominant mutations in the MYH7 and MYBPC3 genes are common causes of inherited cardiomyopathies, which often demonstrate variable phenotypic expression and incomplete penetrance across family members. Biallelic inheritance is rare but allows gaining insights into the genetic mode of action of single variants. Here, we present three cases carrying a loss‐of‐function (LoF) variant in a compound heterozygous state with a missense variant in either MYH7 or MYBPC3 leading to severe cardiomyopathy with left ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…The vast majority of detected VOI were heterozygous, nevertheless; we observed two homozygous ( NEXN , TNNI3 ), and two compound heterozygous ( DSC2 , MYBPC3 ) VOI. In one case, we identified compound heterozygous mutation of MYBPC3 p.S858R with complete deletion of the MYBPC3 gene on the second allele …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The vast majority of detected VOI were heterozygous, nevertheless; we observed two homozygous ( NEXN , TNNI3 ), and two compound heterozygous ( DSC2 , MYBPC3 ) VOI. In one case, we identified compound heterozygous mutation of MYBPC3 p.S858R with complete deletion of the MYBPC3 gene on the second allele …”
Section: Resultsmentioning
confidence: 81%
“…In one case, we identified compound heterozygous mutation of MYBPC3 p.S858R with complete deletion of the MYBPC3 gene on the second allele. 19 T A B L E 2 Genetic variants of 80 index patients with pediatric cardiomyopathy…”
Section: Homozygous/compound Heterozygous Voimentioning
confidence: 99%
“…In another patient with HCM (#23), a pathogenic missense variant in MYH7 was detected in compound heterozygous state with a truncating splice variant in the same gene. A subsequent segregation analysis showed that the truncating variant was not associated with a clinical phenotype in the heterozygous state but led to a severe cardiomyopathy phenotype with non-compaction features in the compound heterozygous state [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of MYH7, the first causative gene for HCM, more than 100 genes have been linked to cardiomyopathies (Geisterfer-Lowrance et al, 1990;Tanigawa et al, 1990;Marian and Braunwald, 2017;Muchtar et al, 2017;Yotti et al, 2019;James et al, 2020). Beyond a monogenic disease, findings from next-generation sequencing (NGS) suggest multiple genetic hits could contribute to phenotypic severity of cardiomyopathies (Xu et al, 2010;Harakalova et al, 2015;Kolokotronis et al, 2019). Both phenotypic and genetic heterogeneity strongly suggest that precision medicine should be practiced to treat cardiomyopathies of various causes (Fatkin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%